Formation Of Ethical And Axiological Competencies When Using Ict In Education - Kabanov Oleg Vladimirovich, Garin Vadim Viktorovich, Pikhota Oleg Igorievich, Snezhko Zoya Victorovna,Kondakchian Nataliia Akopovna (International Journal of Advanced Science and Technology, 2020)
At present, the concept of a competency-based approach to education is gaining ground, which is the basis of substantial changes to ensure that education meets the needs and capabilities of the public in the period of informatization and global mass communication. From the standpoint of the competency-based approach, the meaning of education is the development of the ethical and axiological abilities of students to independently solve problems in various fields and activities based on the use of social experience, an element of which is also the students’ own experience. It is the competency-based approach that is determined by one of the foundations of the "Strategy for the Modernization of Education" - the main state document in the field of Russian education today and in the near future.